(untitled) (The Pretoria Student Law Review, 2023)
The People’s Republic of China (PRC) continues to consolidate its position as one of the most important trade players on the international market. The PRC has signed cooperation agreements with more than 126 countries. It is also a substantial importer of raw materials, intermediate inputs, and other goods. The PRC has dealings with all 54 countries on the African continent, and today the continent ranks as one of the PRC’s most important trading posts. The increasing number of international trade and investment means naturally, that disputes of an international nature will arise between the PRC and African parties. It is for this reason that the China-Africa Joint Arbitration Centre (CAJAC) was established. The formation of CAJAC at the instance of the Forum on China – Africa Cooperation (FOCAC) is to encourage is to administer the resolution of international disputes arising between Chinese and African entities having their principal residence, place of business or nationality located in PRC or a country in Africa. The aim of this article is to examine the salient features of CAJAC which is administer by accredited institutions which include CAJAC Beijing; CAJAC Johannesburg, CAJAC Nairobi, CAJAC OHADA, CAJAC Shanghai and CAJAC Shenzhen.